PENGARUH SUSTAINABILITY REPORT DISCLOSURE TERHADAP KINERJA PERBANKAN - Juwita Puspitandari; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the effect between sustainability report disclosure and performance aspects in sustainability report that is economic, environmental, and social performance on banking performance. The sample used in this research is 13 banking companies that publish a sustainability report from 2013 until 2015. Determination of research sample using purposive sampling method. The data used in this study is secondary data that obtained from the annual report and sustainability report on the banking company. The results of this research show that: sustainability report disclosure has a significant positive effect on banking performance; The economic, environmental, and social performance aspects disclosure in sustainability reports has a significant positive effect on performance.